Synergistic and Additive Interactions of Zhongshengmycin to the Chemical Insecticide Pymetrozine for Controlling Nilaparvata lugens (Hemiptera: Delphacidae) - Zhao, Ruoying; Li, Danting; Wang, Xinlong; Li, Zhong; Yu, Xiaoping; Shentu, Xuping (Frontiers in Physiology, 2022)
Management of the rice brown planthopper Nilaparvata lugens Stål is challenging because it can rapidly adapt to new pesticides within several generations. Combined use of chemical insecticides and antimicrobials was proposed as an alternative strategy to control N. lugens. Our previous experiments identified two effective agents (chemical insecticide: pymetrozine and antimicrobial: zhongshengmycin) that act on different targets in N. lugens. However, conditions and effectiveness of combinations of antimicrobials and insecticides against N. lugens are still unknown. Here, we evaluated separate and combined effects of pymetrozine and zhongshengmycin on third instar nymphs of N. lugens under laboratory and greenhouse conditions. Results showed that zhongshengmycin exerts significant inhibitory effects on the three endosymbionts Pichia guilliermondii, Cryptococcus peneaus, and Pichia anomala cultured in vitro of N. lugens. Combinations of pymetrozine and zhongshengmycin under laboratory conditions produced additive or synergistic effects on N. lugens and caused higher mortality in third instar nymphs than either of them used alone. Experiments under greenhouse conditions further demonstrated that effective component quality ratio of pymetrozine to zhongshengmycin of 1:10 and 1:40 with co-toxicity coefficients of 221.63 and 672.87, respectively, also produced significant synergistic effects against N. lugens. Our results indicated that chemical insecticides combined with antimicrobials may provide a potential novel strategy for controlling N. lugens by inhibiting its endosymbionts.